The Great Patriotic War: to Remember and Understand, Respect and Be Proud (in the Light of Tasks in the Field of Youth Education) - Zoya Sh. Matchanova (Èkonomika, Pedagogika i Pravo, 2015)
In the present article author, in a year of the 70 anniversary of the Victory in the Great Patriotic War, considers questions in the sphere of tasks in the field of education of youth. The author analyzes historical and cultural bases, gives opinions of scientists, analyzes established practices. In summary the author notes, how important to present and future generations to hold in remembrance the Great Patriotic War, the past, the left people. Best of all the main idea lines can transfer Robert Rozhdestvensky: "It is necessary not for the dead, it is necessary live …